Gambaran Format dan Kelengkapan Pengisian Sertifikat Kematian di Rumah Sakit : Sebuah Tinjauan Pustaka - Marwin, Fikri Alhafizd; Susanti, Rika; Fortuna, Fory; Windasari, Noverika; Rustam, Rony; Hasmiwati, Hasmiwati (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Medical Certificate Cause of Death (MCCD) or death certificate is a letter made by the hospital and filled out by the doctor in charge to explain that someone has died. The standard format and instructions for filling out death certificates in Indonesia are issued by the Research and Development Agency of the Ministry of Health, Republic of Indonesia. In practice, several hospitals in Indonesia produce death certificates that do not comply with the standard format and do not follow the instructions for filling out the information issued by the Research and Development Agency of the Ministry of Health, Republic of Indonesia, so that death certificates are often filled out incompletely. This literature review aims to determine the suitability of the format and completeness of filling out a death certificate as well as the factors causing discrepancies and incomplete filling. This research takes the form of a literature review using provider databases, such as Google Scholar and nationally accredited journal sites with the keywords "Medical Cause of Death Certificate (MCCD)", "Death Certificate", and "Death Certificate (SKK)". The results showed that a total of 4 articles were related to the format of death certificates and 8 articles were related to the completeness of filling out death certificates from 2013-2023. Based on the research that has been carried out, it can be concluded that the format of death certificates issued by hospitals in Indonesia still does not follow the standard format of the Research and Development Agency of the Indonesian Ministry of Health. Overall, the completeness of filling out death certificates in several hospitals in Indonesia is still low. Factors causing format discrepancies are the hospital's ignorance of the standard format and the hospital's failure to evaluate and change the death certificate format. Factors causing incomplete filling in are the absence of guidelines for filling out, the absence of regulations and SOPs for filling out death certificates, lack of attention, and quantitative analysis that has not been optimal. Keywords: Medical Certificate Cause of Death, Death Certificate,  Completeness of Filling  ABSTRAK Sertifikat Medis Penyebab Kematian (SMPK) atau sertifikat kematian adalah surat yang dibuat oleh rumah sakit serta diisi oleh dokter penanggung jawab untuk menerangkan bahwa seseorang telah meninggal. Format baku dan petunjuk pengisian sertifikat kematian di Indonesia dikeluarkan oleh Badan Litbangkes Kemenkes Republik Indonesia. Dalam penerapannya, beberapa rumah sakit di Indonesia membuat sertifikat kematian yang tidak sesuai dengan format baku dan tidak mengikuti petunjuk pengisian yang telah dikeluarkan oleh Badan Litbangkes Kemenkes RI sehingga sering didapatkan pengisian sertifikat kematian yang tidak lengkap. Tinjauan pustaka ini bertujuan untuk mengetahui gambaran kesesuaian format dan kelengkapan pengisian sertifikat kematian serta faktor penyebab ketidaksesuaian dan ketidaklengkapan pengisian. Penelitian ini berupa tinjauan pustaka menggunakan database penyedia, seperti google scholar dan situs jurnal terakreditasi nasional dengan kata kunci “Sertifikat Medis Penyebab Kematian (SMPK)”, “Sertifikat Kematian”, dan “Surat Keterangan Kematian (SKK)”. Hasil didapatkan total 4 artikel terkait dengan format sertifikat kematian dan 8 artikel terkait dengan kelengkapan pengisian sertifikat kematian dari rentang tahun 2013-2023. Berdasarkan penelitian-penelitian yang telah dilakukan dapat disimpulkan bahwa format dari sertifikat kematian yang dikeluarkan oleh rumah sakit di Indonesia masih banyak yang belum mengkuti format baku  dari Badan Litbangkes Kementerian Kesehatan RI. Secara keseluruhan, kelengkapan pengisian sertifikat kematian pada beberapa rumah sakit di Indonesia masih rendah. Faktor penyebab ketidaksesuain format adalah ketidaktahuan pihak rumah sakit terhadap format baku serta pihak rumah sakit yang tidak melakukan evaluasi dan perubahan dari format sertifikat kematian. Faktor penyebab ketidaklengkapan pengisian adalah tidak adanya pedoman pengisian, tidak adanya peraturan dan SOP pengisian sertifikat kematian, kurangnya perhatian, dan analisis kuantitatif yang belum optimal. Kata Kunci: Sertifikat Medis Penyebab Kematian, Sertifikat Kematian, Kelengkapan Pengisian